A simple and reproducible prognostic index in luminal ER-positive breast cancers - Castellano, I. (Oxford University Press, 2013)
BACKGROUND: The group of estrogen receptor (ER)-positive breast cancers (both luminal-A and -B) behaves differently from the ER-negative group. At least in early follow-up, ER expression influences positively patients' prognosis. This low aggressive biology flattens out the differences of clinical management. Thus we aimed to produce a prognostic index specific for ER-positive (ERPI) cancers that could be of aid for clinical decision. PATIENTS AND METHODS: The test set comprised 495 consecutive ER-positive breast cancers. Tumor size, number of metastatic lymph nodes and androgen receptor expression were the only independent variables related to disease-specific survival. These variables were used to create the ERPI, which was applied to the entire test set and to selected subpopulations (grade 2 (G2)-tumors, luminal-A and -B breast cancers). A series of 581 ER-positive breast cancers, collected from another hospital, was used to validate ERPI. RESULTS: In the test population, 96.9% of patients classified as ERPI-good showed a good prognosis compared with 79.6% classified as ERPI-poor (P < 0.001). ERPI effectively discriminated outcome in luminal-A and luminal-B and in G2-tumors. In the validation series, the ERPI maintained its value. CONCLUSION: ERPI is a practical tool in refining the prediction of outcome of patients with ER-positive breast cancer.